HUBUNGAN ANTARA PENGAKUAN DAN PEMBERDAYAAN KARYAWAN DENGAN MOTIVASI BERPRESTASI PADA KARYAWAN PT X JOMBANG - Siska Tamara; V. Heru Hariyanto; Listyo Yuwanto (CALYPTRA, 2018)
This research is a quantitative approach through a survey method. The aims of this research is to know how the recognition and empowerment can improve achievement motivation in employees. The population used in this research were employees of PT X Jombang with a total sample of 138 employees. Technique of taking subject sample is using accidental technique. Preliminary data were obtained through interviews of some employees while the main data was obtained through questionnaires. Data analysis used multiple regression analysis and partial correlation. The results showed that the recognition and empowerment of employees is an equally important effort to increase achievement motivation. The greatest contribution to improve achievement motivation in PT X Jombang employees is obtained from the recognition.